Role of UCP1 Gene Variants in Interethnic Differences in the Development of Cardio-Metabolic Diseases - Flouris, Andreas D.; Shidlovskii, Yulii V.; Shaposhnikov, Alexander V.; Yepiskoposyan, Levon; Nadolnik, Liliya; Karabon, Lidia; Kowalska, Anna; Carrillo, Andres E.; Metsios, George S.; Sakellariou, Paraskevi (Frontiers in Genetics, 2017)
Cardio-metabolic diseases (CMDs) comprise a cluster of risk factors that contribute to chronic pathological conditions with adverse consequences for cardiovascular function and metabolic processes. A wide range of CMD prevalence rates among different ethnic groups has been documented. In view of accumulated evidence, there is a trend toward increasing CMD prevalence rates in Eastern Europe and Western Asia. Numerous studies have revealed an association between uncoupling protein 1 (UCP1) gene variants and CMDs. UCP1 activity is essential for brown adipose tissue (BAT)-mediated thermogenesis. Experimental animal studies and epidemiological studies in humans highlight the significance of BAT-mediated thermogenesis in protecting against obesity and maintaining a lean phenotype. We hypothesize that the genetic variation in UCP1 gene expression observed among different ethnic groups could contribute to the ethnic-specific predisposition to CMD development. Constructing such prevalence maps of UCP1 gene variants could contribute significantly into identifying high-risk ethnic groups predisposed to the development of CMDs, and further shaping public health policies by the improvement of existing preventive and management strategies.